KONCEPCE DVOUSYSTÉMOVÉHO VOZIDLA UMOŽŇUJÍCÍHO BEZPŘESTUPOVOU VAZBU EXTRAVILÁNU A INTRAVILÁNU MĚSTA KARLSRUHE (Perner's Contacts, 2007)
As experiences have shown, the point use of existing regional railway lines by local passenger rail transit vehicles is technically possible in principle. Although calling for a degree of outlay for specific adaptation measures that involve structures and/or vehicles, this outlay is small in comparison to the cost of building a genuine rail rapid transit system from scratch. From a technical perspective, however, operating one or other distinctive rail mode is always the ideal scenario. This alone enables the precise co-ordination of complete components with one another (in particular, platforms and vehicles). Compared to single-mode operation, to a certain degree hybrid operation represents a type of “emergency remedy”, within which compromises have to be struck between two “naturally” different rail systems.
Keywords: railway lines; passenger transport; Karlsruhe; hybrid operation; rail vehicle